Do governance and digital infrastructure support Asean-5 business growth? - Prestianawati, Silvi Asna; Setyanti, Axellina Muara (C-DISC, 2023)
ASEAN is one of the fastest growing economies in the world and is one of the five largest economies in the world after the US, EU, China, and Japan. ASEAN-5, the founding countries of Indonesia, Malaysia, the Philippines, Singapore, and Thailand (